Hydrate-induced clogging of sand-control screen and its implication on hydrate production operation. (1st September 2020) - Li, Yanlong; Wu, Nengyou; Ning, Fulong; Gao, Deli; Hao, Xiluo; Chen, Qiang; Liu, Changling; Sun, Jianye
Abstract: Blockage of sand-control media is one of the main obstacles that affect gas production efficiency from gas hydrate-bearing sediments. Hydrate reformation is a potential plugging inducer of sand-control media. In this study, we conduct a series of experiments using steel-wired screen mesh to examine the hydrate-induced clogging of sand-control screen. The screen mesh sample was installed into a closed-circuit circulating system under gas-water two-phase flow condition to simulate bottomhole multiphase production processes. The results indicate that hydrate formation within the screen would causes permeability loss of the screen up to 98%. The pseudo-permeability of the screen sample shows dual-gradient decreasing characteristics during hydrate clogging. Therefore, we speculate that hydrate accumulating and hydrate particle bridging are the two main mechanisms causing screen plugging. The hydrate accumulating sub-process is mainly controlled by the degree of subcooling, while the hydrate particle-bridging sub-process is affected by fluid flow rate. Furthermore, the " J -shape" coiling of pressure-temperature relationship can be used as an indicator in diagnosing possible bottomhole screen plug during hydrate exploitation. Artificial interference of downhole temperature is strongly recommended to mitigate screen plugging induced by hydrate reformation. Highlights: Hydrate clogging causes permeability loss of sand-control screen up to 98%. Hydrate accumulation causes dual-gradient decrease in the permeability of sand-control screen. The " J -shape" coiling of P - T curve is a indicator to diagnose downhole hydrate-induced screen clogging. Artificial temperature interference is recommended to mitigate hydrate induced screen clogging.